Reasonableness (the principle of) - Stamile, Natalina (EUNOMÍA. Revista en Cultura de la Legalidad, 2015)
The aim of this study is to highlight the different uses of the reasonableness in law. Even if the concept of reasonableness has vague and ill-defined contours, it seems to have “two souls”, one deriving from case law while the other is more theoretical-philosophical nature. Particular attention is given to determining not only the nature and origins of the reasonableness but also and especially to explaining the duality inherent in this concept. The analysis begins with a focus on reasonableness within Legal Reasoning with reference to the theory formulated by Robert Alexy, who defines the legal question as a special case in the general practical discourse. Moreover, in order to support and contribute to the recent affirmation of the independence and autonomy of reasonableness with regards to, for example, the principle of equality in public law, within legal doctrine and the case law, we analyze some “new” connections, such as those between reasonableness and the private field. Finally, we attempt to show that, through its development in fields of law outside the public one, reasonableness is omnipresent in law.